Rheological Behaviors and Properties of Poly (Ether Ether Ketone) In-Situ Blends: Effect of Chemical Structure of Added Thermotropic Liquid Crystalline Polyarylates. Issue 12 (2nd December 2019) - Chen, Gong; Chen, Peng; Zeng, Luxian; Xu, Jianjun; Liu, Pengqing
Abstract: Two kinds of thermotropic liquid crystalline polyesters (TLCP) with different chemical structures were used as flow modifiers during the melt spinning of poly (ether ether ketone). One of TLCPs, named PAT-S, was a kind of aromatic polyester synthesized from 4-acetoxybenzoicacid and 6-hydroxy-naphthoic acid, and the other one named, PEEKAR, was a block copolymer based on poly (ether ether ketene) (PEEK) oligomers and PAT-S oligomers. The effects of the chemical structures of the prepared TLCPs on the rheological behavior of the TLCP/PEEK blends were measured by rheological measurements, and then the structure and properties of the TLCP/PEEK in-situ blend fibers were studied by a series of methods, including differential scanning calorimetry (DSC), wide angle X-ray diffraction (WRXD), optical microscopy (OM), scanning electron microscopy (SEM), orientation degree tests, mechanical properties tests, etc. The results showed that the melt viscosity of PEEK could be effectively reduced by nearly 20% by adding a small amount of PEEKAR or PAT-S with the viscosity reducing effect of PEEKAR on PEEK being greater than that of PAT-S; this was mainly caused by the better compatibility between PEEK and PEEKAR because of the similar segment structures. The crystallinity of the PEEK fibers increased by nearly 50% with addition of both TLCPs, indicating that both the PEEKAR and PAT-S could serve as nucleating agent as well. The results from the morphology analysis clearly proved that PEEKAR had a better compatibility with the PEEK resin compared with PAT-S. The tensile strength of the PEEK fibers could be improved to some extent by adding PEEKAR, while it was obviously reduced after adding PAT-S.